Analysis of body composition and body function of athletes in freestyle ski half-pipe national team - Li, L.; Wu, H. (Exercise Biochemistry Review, 2018)
Objective The objectives were to analyze the body composition and body functions of the freestyle ski half-pipe national team athletes, to understand the body composition characteristics of the athletes , and to explore the relationship between body composition and body function in the sports program, in preparation for 2022 The Winter Olympics provides a theoretical reference.